Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/jbc.m113.491803
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of MicroRNA (miRNA) Targets in Breast Cancer Cells

Abstract: Background: miRNA deregulation contributes to tumor progression. Results: Endogenous miRNA targets were identified in two breast cancer cell lines by integrated analysis of miRNA/mRNA expression and miRNA-mRNA interaction. Conclusion: miRNAs collectively function to promote survival but suppress cell migration/invasion. Significance: The defined endogenous miRNA targets will facilitate future studies to link miRNA deregulation with breast cancer cell properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…miRNAs have been increasingly recognized as key regulators of metastasis [27]. We previously showed that DROSHA knockdown promoted lung metastasis of basal-like breast cancer cells (MDA-MB-231) in an orthotopic xenograft model, suggesting a role of DROSHA-dependent miRNAs in repressing metastasis [28]. Therefore, we examined whether specific miRNAs play a role in regulating the expression of pro-metastatic genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have been increasingly recognized as key regulators of metastasis [27]. We previously showed that DROSHA knockdown promoted lung metastasis of basal-like breast cancer cells (MDA-MB-231) in an orthotopic xenograft model, suggesting a role of DROSHA-dependent miRNAs in repressing metastasis [28]. Therefore, we examined whether specific miRNAs play a role in regulating the expression of pro-metastatic genes.…”
Section: Resultsmentioning
confidence: 99%
“…To examine metastases in lungs, the dorsal surface of the left lung lobe was imaged using a fluorescent microscope at 10× magnification (NIKON, CFI60), and metastatic foci of mCherry expressing cells were quantified using ImageJ program [53]. The presence of tumor cells in the left lobes was further confirmed by Hematoxylin and Eosin (H&E) staining of formalin-fixed lung sections (10 μM thick) as described previously [28]. All animal studies adhered to protocols approved by the Institutional Animal Care and Use Committee of University of Tennessee Health Science Center.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies estimate miRNAs regulate ≥60% of the human protein-coding transcriptome(11). Importantly, single miRNAs can regulate entire cell signaling networks in a cell-context dependent manner(12). Since miRNAs can function as oncogenes or tumor suppressors, and can control the robustness of multiple cell signaling pathways(13,14), miRNAs that become dysregulated could promote a disease state, such as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For JNK knockdown, cells were transfected with ON-TARGETplus siRNA (20 nmol/L; Dharmacon), targeting JNK1 or JNK2 isoforms individually or in combination, and in order to activate JNK signaling, cells were transfected with constitutively active MKK7 and MEKK1 constructs. Immunoprecipitation (IP) of the AGO2 protein was carried out as previously described (36).…”
Section: Transient Transfections and Immunoprecipitationmentioning
confidence: 99%